2022
DOI: 10.1161/circulationaha.121.057793
|View full text |Cite
|
Sign up to set email alerts
|

Routine Pressure Wire Assessment Versus Conventional Angiography in the Management of Patients With Coronary Artery Disease: The RIPCORD 2 Trial

Abstract: Background: Measurement of fractional flow reserve (FFR) has an established role in guiding percutaneous coronary intervention. We tested the hypothesis that, at the stage of diagnostic invasive coronary angiography, systematic FFR-guided assessment of coronary artery disease would be superior, in terms of resource use and quality of life, to assessment by angiography alone. Methods: We performed an open-label, randomized, controlled trial in 17 UK cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 21 publications
0
36
1
Order By: Relevance
“…They found that more targeted invasive management can reduce healthcare resource costs without compromising patient outcomes which drove them to conclude that FFR-guided management of NSTEMI may be a cost-effective strategy over standard angiography. Unlike the results of the RIPCORD 2 trial [14], the cost savings they found were due to absolute, but non-significant, reductions in length of stay and health events such as revascularizations, re-hospitalizations, myocardial infarction and stroke events. However, due to the small sample size and the need for longer follow up, there still remains considerable decision uncertainty [16].…”
Section: Fig 2 Impact Of Number Of Vessels Examined With Pressure Wir...contrasting
confidence: 58%
See 3 more Smart Citations
“…They found that more targeted invasive management can reduce healthcare resource costs without compromising patient outcomes which drove them to conclude that FFR-guided management of NSTEMI may be a cost-effective strategy over standard angiography. Unlike the results of the RIPCORD 2 trial [14], the cost savings they found were due to absolute, but non-significant, reductions in length of stay and health events such as revascularizations, re-hospitalizations, myocardial infarction and stroke events. However, due to the small sample size and the need for longer follow up, there still remains considerable decision uncertainty [16].…”
Section: Fig 2 Impact Of Number Of Vessels Examined With Pressure Wir...contrasting
confidence: 58%
“…The study proved that, over a one year follow up period, routine systematic FFR use was cost neutral compared with angiographic guidance alone and was not associated with significant differences in quality of life or angina status after 1 year of follow up. These costs were calculated based on the NHS Tariff system and included the costs starting from the index procedure and all subsequent hospital admissions, outpatient visits, and accident and emergency department attendance over the following year [14]. * Group 0 includes n=3 cross-over patients initially randomized to FFR group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to European and American recommendations, FFR should be used in patients without documented evidence of myocardial ischemia and/or patients with intermediate coronary lesions [ 5 , 6 ]. After the positive results produced in the one-year data of the “Fractional Flow Reserve Versus Angiography for Multivessel Evaluation” (FAME) study [ 7 ], several randomized clinical trials (RCTs) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and non-randomized [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] studies investigated the effectiveness of FFR in improving clinical outcomes. Overall, despite data from non-randomized studies strongly supporting the benefit of an FFR-guided revascularization strategy compared to isolated angiography in terms of the clinical endpoint, several RCTs have reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%